Piezoelectric Sensors Placement Strategy for Accurate Acoustic Data Evaluation in Cavitation-induced Erosion Processes - A. Nasseroleslami; A. Sarreshtehdari; M. S. Seif (Journal of Applied Fluid Mechanics)
Evaluation of cavitation erosion risk, whether through numerical (CFD) or experimental methods, is crucial in many fluid flow design processes. This risk correlates directly with cavitation signals on affected surfaces. The aim of this study is to optimize the placement of piezoelectric sensors to investigate cavitation-induced erosion on solid surfaces and to enhance the numerical evaluation of their correlation with recorded signals from the sensors. In this study, based on the technical specifications of the K23 tunnel, a convergent-divergent channel has been designed to reduce the pressure in its test section below the vapor pressure, thereby creating the potential for bubble formation on the sample plate. Within this channel, four semi-cylindrical bluff bodies have been utilized as the most effective obstacles to increase cavitation erosion. A quick method for identifying cavitation erosion involves applying a special color to the sample plate. The Film Applicator has been employed as the optimal tool for achieving a uniform color and a thin paint layer on the sample plate. Through CFD modeling, potential cavitation zones are identified under various test conditions to refine the placement of piezoelectric sensors in experimental tests. As a result, piezoelectric sensors are positioned more accurately to measure sound pressure levels. The sound pressure levels obtained using piezoelectric sensors in the time domain, are compared with erosion-induced cavitation zones on the sample test surfaces. The strong agreement between sound pressure levels and observed erosion on the sample plates confirms the accuracy and improvement in the placement of piezoelectric sensors based on CFD modeling.